Tasawuf antara Kesalehan Individu dan Dimensi Sosial - Nurcholis, Ahmad (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2011)
Within this modern era where Islamic doctrines have been more eroded by the advance of scientific development, the power of umma has gradually decreased as a result of abandonment of spirit of jihâd al-nafs. There would be no any other way except to revive the principles and values of Islamic Sufism without leaving rational way of thinking and escaping from social realities. When human recognize their God it would be, then, easier for them to perform everything God commands to them. Where did human come from and where they will go to are among philosophical questions that should be traced by the Sufi. These are foundations for the Sufis to ?recognize their selves?, since by recognizing the self God can be, then, recognized. Tasawuf is a way, which leads to qalb salîm (a pure heart). Many classic books discuss this and the discussion deals with: firstly, efforts to straighten deeds, khushû?, and courtesy of worship; secondly, ways of mujâhadah, self and heart purification, and abolishing madhmûmah (bad manners) and replacing them with mahmûdah (commendable conducts); thirdly, ma?rifat, rabbânîyah, wahbîyah knowledge, dhawq, wijdânîyah, and nature of kashf.